Aplicación de índices bióticos en la evaluación de la calidad del agua en sistemas lóticos de la llanura pampeana argentina a partir del empleo de diatomeas - Licursi, Magdalena (2004)
Diatoms are useful ecological indicators because they are found in abundance in most lotic ecosystems. The use of diatoms as indicators of the quality of river waters is widely accepted based on the fact that all diatom species have optima with respect to their tolerance for environmental conditions such as nutrients, organic pollution, pH, etc. Moreover diatoms are indicators of pollution in short term compared with other groups eg. macroinvertebrates. The rivers and streams of the Pampean plain, in Buenos Aires Province, are subjected to different human impacts. The most important stresses on rivers and streams in the Pampean plain are organic enrichments (discharge of insufficiently treated sewage), nutrients, heavy metals, pathogenic agents, pesticides, herbicides and physical changes produced by dredging and canalisation. The bottom substrate is mostly composed of slime-clay with low proportions of gravel and sand; in consequence, the epipelon is the most represented benthic community and suitable for biomonitoring purposes because it allows for comparing similar substrates along the rivers and streams. The aim of this study is to summarise the most common methodologies used in biomonitoring with diatoms and the application of biotic indices (diversity and pollution indices) in the evaluation of water quality of rivers and streams from the Pampean plain.